2007
DOI: 10.1027/0227-5910.28.4.211
|View full text |Cite
|
Sign up to set email alerts
|

Current Understandings of Suicide Survivor Issues: Research, Practice, and Plans

Abstract: The goals of the Postvention Taskforce of the International Association for Suicide Prevention (IASP) are to increase awareness of postvention and survivor issues. One of the strategies is to organize meetings. We report on the 1st International Suicide Postvention Seminar, held as a 1-day preevent at the 11th European Symposium on Suicide and Suicidal Behavior in Portoroz, Slovenia, September 2006. The seminar provided a state of the art review of the postvention field, with plenary presentations on research,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Several previous studies have demonstrated that performing postvention for the suicide survivors has a positive association with lower post-traumatic symptomatology. 29 30 Furthermore, postvention may prevent acting out of unspoken trauma and suicidality among the potentially bereaved and depressed adolescents exposed to suicide. 31…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have demonstrated that performing postvention for the suicide survivors has a positive association with lower post-traumatic symptomatology. 29 30 Furthermore, postvention may prevent acting out of unspoken trauma and suicidality among the potentially bereaved and depressed adolescents exposed to suicide. 31…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, it is plausible that experience with suicide attempts and willingness to support a family member's decision to request PAS reflect an understanding of how someone could get to a point in their life where death is a favorable outcome, yielding empathy with that person's wishes. However, the suicide survivors in the sample (i.e., individuals having lost someone close to them by suicide) know firsthand the emotional and psychological distress experienced following a suicide (Andriessen, Beautrais, Grad, Brockmann, & Simkin, 2007;Mitchell, Kim, Prigerson, & Mortimer-Stephens, 2004;Grad, 1996) and may not want to burden others with that type of loss, thus rendering them less likely to recommend competence.…”
Section: Impact Of Clinician's Personal Values Characteristicsmentioning
confidence: 99%
“…Moreover, the specific nature of bereavement by suicide often makes it difficult for bereaved individuals to seek help. Also, until recently, few resources were readily available (Andriessen et al, 2007). Self-help groups are one means of getting support (Andriessen & Farberow, 2002), but not all people will want to use this form of help or indeed are aware of it.…”
Section: K E I T H H a W T O N S U E S I M K I N A N D S I A N R E E Smentioning
confidence: 99%
“…Some content of this report is based, with permission of Hogrefe & Huber, on a report published in Crisis (Andriessen et al, 2007 …”
Section: Acknowledgementsmentioning
confidence: 99%